The origin of life from the geological conception - Campoblanco Díaz, Honorio (2001)
Explain the processes and mechanisms of the origin of life is a very complex issue , given the diversity of variables , factors, energy and thermodynamic conditions involved , there are many well-founded theories and hypotheses , however there are still many unknowns that make us think that life also been influenced imperceptibly energies constantly changing and evolving, currently the existence of " force fields " as the electric field, magnetic , electromagnetic, nuclear, gravitational field of the stars that strongly influence the constitution is verified biological , mental and spiritual living beings. From the geological conception life is designed from the first energy reactions of incandescent material, and the resulting chemical reactions , thermochemistry chemical broth loaded with isotopes and chemical elements released by volcanoes 3,600 million years ago in the process degassing of the mantle , which associated with electric shock , lightning and thunder accompanying such energetic events , made ​​possible the first abiotic reactions reported by Miller and Urey , forming increasingly complex chemical compounds , the same that were subsequently accelerated , repowering and / or canceled for extrasolar powerful energy flows , from the vastness of the universe , galaxies, novae and supernovae , directing to these chemical and thermochemical form new increasingly complex chemicals (proteins , amino acids ) and then by an energy jump reactions give rise to life. In summary, it can be argued that life is a stage of vibratory fruit stuff interact expansive and compressive energy from the sun, the interior of the earth , the powerful and fleeting energy flows from the cosmos. Rudolf Steiner calls these interactions as " Rhythms " formed by a set of vital processes , organized and somewhat semiespirtuales supersensible , which we can not perceive its immediate effects . The earth as a whole, not only receives energy pulses from the outside, but turn metered conjugated , such energetic rhythms interacts with energy flows emanating from inside, as the magnetic field , gravitational , electrical, electromagnetic etc. . generating imperceptible changes and modifications in living beings. Even the materials of the mineral kingdom , showing the effects of the influences and variations of such fields. These energy rates are not worth this , their alternation is repeated over time on a daily, weekly, yearly , in centuries or millennia as part of the geological evolution .